2018
DOI: 10.1002/jmv.25241
|View full text |Cite
|
Sign up to set email alerts
|

Scoring system for risk stratification of viral reactivation during prophylactic antiviral treatment in Korean patients with hepatitis B undergoing anticancer chemotherapy: A multicenter study

Abstract: Prophylactic antiviral therapy is recommended for hepatitis B virus (HBV)-infected patients with malignancies who are undergoing systemic chemotherapy. In the current study, we aimed to develop a risk scoring system to guide the selection of prophylactic antiviral agents. In this retrospective analysis, we included consecutive chronic hepatitis B patients who received antiviral prophylaxis for chemotherapy of solid or hematologic malignancies at three large-volume hospitals in Korea. The primary endpoint was H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In a retrospective comparative analysis of 419 CHB patients who received chemotherapy for solid cancers and lymphoma in Korea, HBeAg positivity, serum HBV DNA, and cancer types were identified as risk factors related to hepatitis B reactivation, and a risk stratification tool was developed based these factors. This study also confirmed that entecavir had a better preventive effect than lamivudine or telbivudine in the high-risk group [ 400 ]. However, since most prophylactic therapy studies were conducted on lymphoma patients, prospective studies evaluating various malignancies including solid cancers on appropriate antiviral agents and treatment duration for each cancer type and anticancer drug are needed.…”
Section: Management In Special Conditionssupporting
confidence: 77%
“…In a retrospective comparative analysis of 419 CHB patients who received chemotherapy for solid cancers and lymphoma in Korea, HBeAg positivity, serum HBV DNA, and cancer types were identified as risk factors related to hepatitis B reactivation, and a risk stratification tool was developed based these factors. This study also confirmed that entecavir had a better preventive effect than lamivudine or telbivudine in the high-risk group [ 400 ]. However, since most prophylactic therapy studies were conducted on lymphoma patients, prospective studies evaluating various malignancies including solid cancers on appropriate antiviral agents and treatment duration for each cancer type and anticancer drug are needed.…”
Section: Management In Special Conditionssupporting
confidence: 77%
“…16,17,29,33,34 HBV reactivation is a common complication in patients who undergo antitumor treatment, which may lead to antitumor treatment delays or discontinuation. [35][36][37][38] Among CHB patients with solid tumors without receiving antiviral 2128 treatment, the risk of HBV reactivation due to antitumor therapy was 25%. 35 Antiviral treatment can significantly reduce the occurrence of HBV reactivation after the treatment of the malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…These screening tests should be repeated at least 30 days before HDC/ASCT. Monitoring of HBV viral load is strongly recommended in HBsAg and/or anti-HBc antibody positive patients for 6 months after HDC/ASCT, as immunosuppression can lead to viral reactivation and disease [41][42][43][44][45]. If maintenance therapy using rituximab, lenalidomide or bortezomib is administered, monitoring should be continued for 6 months following cessation of the respective maintenance therapy.…”
Section: Diagnostic Procedures Before the Onset Of Fever Or Infectionmentioning
confidence: 99%